TRIBOLOGICAL CHARACTERISTICS OF NITRIDED IN PLASMA GLOW DISCHARGE SAMPLES FROM TITANIUM ALLOY VT5 IN PAIRS WITH DIFFERENT MATERIALS - Сагалович, Олексій; Сагалович, Владислав; Попов, Віктор; Дуднік, Станіслав; Олійник, Олександр (Problems of Friction and Wear, 2022)
One of the modern methods of improving operating characteristics of titanium and titanium-based alloys under conditions of friction and increased contact loads is the method of ion-plasma nitriding. The effect of nitriding of VT5 alloy in the plasma of a glow discharge excited in a hollow cathode on its tribological characteristics in pairs with different materials in T-1 fuel and under dry friction conditions has been studied. For research and tribological tests, samples of VT5 alloy were nitrided in the plasma of a glow discharge excited in a hollow cathode at a temperature of 975 ± 15 ° C and a pressure of 58 ± 2 PA in a nitrogen-argon gas mixture with a nitrogen content of 78 %. Studies of samples of BT5 alloy after nitriding showed that the surface roughness Ra was in the range of 0.58-0.64, and the surface hardness HV5 was 525 ± 20 kgf/mm² at a base hardness of 325 ± 15 kgf/mm². Tribological tests were performed on a friction machine 2070 SMT-1 according to the scheme "cube - roller". Tests under conditions of friction with oil were performed at a load of 200 N. The sliding speed during the tests was 1.3 m/s, the test time was 75 sec. The test under dry friction conditions was carried out at a load of 100 N and a sliding speed of 0.785 m / s, the test time was 30 minutes. Low wear ability in relation to the nitrided titanium alloy VT5 (<2.4x10-4 mm3 / sec), as well as friction coefficients at the level of 0.08 to 0.12 in the order of their growth had bronze BrSu3N3Ts3S20F0,2, Br.O10S2NZ, BrSu6F0,9, steel SHH-15, cast iron VCH2169-2, cemented steel 20H3MVF.